2011
DOI: 10.1093/molehr/gar047
|View full text |Cite
|
Sign up to set email alerts
|

Development of ovarian hyperstimulation syndrome: interrogation of key proteins and biological processes in human follicular fluid of women undergoing in vitro fertilization

Abstract: Ovarian hyperstimulation syndrome (OHSS) is an iatrogenic complication and potentially life-threatening condition resulting from excessive ovarian stimulation during assisted reproductive technologies. Our aim was to identify candidate proteins in follicular fluid (FF) using various proteomic approaches which may help to identify patients at risk of OHSS. We analysed the proteome alterations in FF from patients suffering from severe forms of OHSS (OHSS+) compared with a control group of women without or with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…The P-value was calculated using the righttailed Fisher's exact test. Bars represent − log (P-value) for significance ovarian stimulation has been demonstrated to induce aberrant expression of FF proteins, such as C3, associated with inflammation, iron transport and storage, blood coagulation, and innate immunity in women who developed ovarian hyperstimulation syndrome [28]. In this study, the increased levels of C3 and ZAG in the COH FF suggest that the patients might have had aberrant immune and inflammatory responses during the cycle.…”
Section: Discussionmentioning
confidence: 68%
“…The P-value was calculated using the righttailed Fisher's exact test. Bars represent − log (P-value) for significance ovarian stimulation has been demonstrated to induce aberrant expression of FF proteins, such as C3, associated with inflammation, iron transport and storage, blood coagulation, and innate immunity in women who developed ovarian hyperstimulation syndrome [28]. In this study, the increased levels of C3 and ZAG in the COH FF suggest that the patients might have had aberrant immune and inflammatory responses during the cycle.…”
Section: Discussionmentioning
confidence: 68%
“…In a recent study by Bianchi et al in the follicular fluid of six women undergoing IVF after ovarian hyperstimulation, 43 unique proteins were identified, functionally classified in 5 groups (inflammation and regulation of acute-phase, complement and coagulation, response to wounding, protein-lipid complex/lipid metabolism and transport, and cytoskeleton organization) and cross-linked to generate a tightly controlled pathway depicting the initial inflammatory-like phase of ovulation, also described in previous studies (87,88), further accentuated by ART superovulation, followed by tissue remodeling that is crucial for the formation of corpus luteum. A1 antithrypsin was differentially expressed in the follicular fluid and sera of women in this cohort (89).…”
Section: Proteomics and Oocytementioning
confidence: 83%
“…The regulation of C3 expression in malignant cells is not well understood, similarly, the involvements of the cascade in the innate immunity of follicular fluids still need to be explored. Jarkovska et al (2011) have shown the role of complement in oocyte maturation. They demonstrated that activation of complement resulted in the deficiency of vascular endothelial growth factor (VEGF), in fact VEGF is needed for oocyte maturation.…”
Section: Resultsmentioning
confidence: 99%